IEEE International Frequency Control Sympposium and PDA Exhibition Jointly With the 17th European Frequency and Time Forum, 200
DOI: 10.1109/freq.2003.1275111
|View full text |Cite
|
Sign up to set email alerts
|

First results of real-time time and frequency transfer using GPS code and carrier phase observations

Abstract: We have used code and carrier phase data from the Global Positioning System (GPS) satellites to estimate time differences between atomic clocks in near (< 10 s) real-time. For some sites we have used data transmitted via Internet connections and TCP/IP, while for other sites data were collected in deferred time, but processed by a Kalman filterbased software as if they were available in real time. Satellite orbit and clock data of different quality have been used. The real-time estimates of time differences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The terms with tilde represent the quantities obtained by prediction and the terms with caret represent the quantities obtained by measurement update. Equation (7) shows the measurement update of the estimate error covariance combined with covariance x-reduction. Assuming that n is the number of the member clocks and the two-state clock model is used for each member clock, S becomes a 2n × 2n identity matrix with diagonal elements that correspond to the individual clock phases set to zero [13].…”
Section: Kalman Filter-based Ensemble Clockmentioning
confidence: 99%
See 1 more Smart Citation
“…The terms with tilde represent the quantities obtained by prediction and the terms with caret represent the quantities obtained by measurement update. Equation (7) shows the measurement update of the estimate error covariance combined with covariance x-reduction. Assuming that n is the number of the member clocks and the two-state clock model is used for each member clock, S becomes a 2n × 2n identity matrix with diagonal elements that correspond to the individual clock phases set to zero [13].…”
Section: Kalman Filter-based Ensemble Clockmentioning
confidence: 99%
“…Some other studies made use of GPS CP in realtime frequency transfer [5,6] and their strategies were based on time differencing of the CP signal. Another study tested various solution strategies for real-time time and frequency transfer using the GPS CP measurements and concluded that among the real-time solutions tested, the common-view-type real-time solution yielded the best agreement with the postprocessed solution [7].…”
Section: Introductionmentioning
confidence: 99%
“…[1]. The limit for real time solutions is about 100 ps [2]. Uncertainties due to temperature-induced delays can accumulate up to several 100 ps or even to the ns level for a badly controlled system, see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, they used the observed part of the ultra-rapid ephemeris rather than the predicted part, which is not possible in real-time applications. Another study tested various solution strategies for real-time time and frequency transfer using the GPS CP measurements and concluded that among the realtime solutions tested, the common-view (CV) type real-time solution yielded the best agreement with the post-processed solution [11].…”
Section: Introductionmentioning
confidence: 99%